Surgical Management of Patellar Luxation in a Dog - Saharan, Sandeep; Poonia, Anju; Kumar, Amit; Sachin,; Tiwari, Deepak Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
In dogs, patellar luxation is a common orthopedic problem. The luxation can be lateral, medial, or bidirectional.  Medial and lateral luxation is usually diagnosed in small breed and giant breed dogs, respectively (Bosio et al.,  2017). Patellar luxation is the result of various anatomic  abnormalities involving the entire hind limb. The absence  of the physiological pressure on the articular cartilage of the  trochlear groove due to chronically luxated patella during  growth may prevent the development of an adequately deep  and wide groove (trochlear hypoplasia) (Lavrijsen et al., 2014).  The correction of the luxation can be accomplished through  the use of both soft tissue and osseous surgical methods  or a combination of more than one procedure (Harsen,  2006). Soft tissue procedures include lateral imbrications,  antirotational sutures and medial desmotomy. These  techniques can be performed on immature individuals to  reduce aberrant forces  on growing bones and on mature  patients to support bony procedures (Di Dona et al., 2018).  Bony procedures include Tibial tuberosity transposition,  Corrective osteotomies  and Deepening of the trochlear  groove by abrasion trochleoplasty, trochlear chondroplasty,  wedge and block recession trochleoplasty. The goal of the  repair is to repose the tendon’s insertion between the patella  and tibia in order to create a trochlear groove that is deep  and wide enough to embed about 50% of the patella above  the trochlear ridges (Talcott et al., 2000).
Keywords: physiological parameters; osteotomy; weighing